COVID‐19 patients with documented alcohol use disorder or alcohol‐related complications are more likely to be hospitalized and have higher all‐cause mortality. (2nd May 2022) - Bailey, Kristina L.; Sayles, Harlan; Campbell, James; Khalid, Neha; Anglim, Madyson; Ponce, Jana; Wyatt, Todd A.; McClay, James C.; Burnham, Ellen L.; Anzalone, Alfred; Hanson, Corrine
Abstract: Background: Coronavirus Disease 2019 (COVID‐19) has affected every country globally, with hundreds of millions of people infected with the SARS‐CoV‐2 virus and over 6 million deaths to date. It is unknown how alcohol use disorder (AUD) affects the severity and mortality of COVID‐19. AUD is known to increase the severity and mortality of bacterial pneumonia and the risk of developing acute respiratory distress syndrome. Our objective is to determine whether individuals with AUD have increased severity and mortality from COVID‐19. Methods: We utilized a retrospective cohort study of inpatients and outpatients from 44 centers participating in the National COVID Cohort Collaborative. All were adult COVID‐19 patients with and without documented AUDs. Results: We identified 25, 583 COVID‐19 patients with an AUD and 1, 309, 445 without. In unadjusted comparisons, those with AUD had higher odds of hospitalization (odds ratio [OR] 2.00, 95% confidence interval [CI] 1.94 to 2.06, p < 0.001). After adjustment for age, sex, race/ethnicity, smoking, body mass index, and comorbidities, individuals with an AUD still had higher odds of requiring hospitalization (adjusted OR [aOR] 1.51, CI 1.46 to 1.56, p < 0.001). In unadjusted comparisons, individuals with AUD had higher odds of all‐cause mortality (OR 2.18, CI 2.05 to 2.31, p < 0.001). After adjustment as above, individuals with an AUD still had higher odds of all‐cause mortality (aOR 1.55, CI 1.46 to 1.65, p < 0.001). Conclusion: This work suggests that AUD can increase the severity and mortality of COVID‐19 infection. This reinforces the need for clinicians to obtain an accurate alcohol history from patients hospitalized with COVID‐19. For this study, our results are limited by an inability to quantify the daily drinking habits of the participants. Studies are needed to determine the mechanisms by which AUD increases the severity and mortality of COVID‐19. Abstract : We identified a retrospective cohort of adult COVID‐19 patients with documented AUD (n=25, 583) and without AUD (n=1, 309, 445). In unadjusted comparisons, those with AUD were more likely to be hospitalized (OR 2.00) and had higher mortality (OR 2.18). After adjusting for age, sex, race/ethnicity, smoking, BMI, and comorbidities, those with an AUD were 1.51 times more likely to be hospitalized and 1.55 times more likely to die. This work suggests that AUD can increase the severity and mortality of COVID‐19 infection.